SPECIFIC ASPECTS OF THE USE OF DIGITAL TECHNOLOGIES AND PLATFORMS IN THE STUDY OF NATIONAL SPIRITUAL HERITAGE - o‘g‘li, Kozimov Azizjon Nozim; o‘g‘li, Rahimjonov Shoxruxmirzo Shuxrat (Research Focus International Scientific Journal, 2026)
This article discusses the specific aspects of using digital technologies and platforms in the study of national spiritual heritage. The article analyzes the correct implementation of electronic educational resources based on digital technologies in the development of our country, as well as the systematic and interactive acquisition of knowledge about national spiritual heritage through electronic textbooks, multimedia textbooks, virtual libraries and online platforms.